REFLECTION OF CULTURE IN LEGAL RHETORIC (TAMADDUN NURI JURNALI, 2024)
This article analyzes the cultural expressions used in the speech of English and Uzbek lawyers and shows how to increase the effectiveness of the defense speech by using them.